The effect of shrinkage on company performance: case of Choppies supermarket Mkoba branch - Vhenge, Wiseman K. (Midlands State University, 2017)
This dissertation was on the effect of shrinkage on company performance. It meant to analyse how shrinkage is affecting the company as shrinkage has been on the rise since the economic and aggregate demand collapse. The main research objectives were determining the effects of physical stock loss on sales, to determine the effects of process failure on service delivery, establish the effects of value discrepancy on profitability and to determine the effects of intercompany fraud on cost efficiency. Accredited scholars and journals were used to gain explicit understanding of the topic under review. A descriptive research and explanatory research was used to describe and explain how shrinkage affects Choppies superstore performance. For primary data collection; interviews and questionnaires were employed to gather data. The questionnaires distributed were 34 and 32 were answered and returned giving a 94% authentic rating. Interviews booked were 4 and 3 were carried out giving a 75% authenticity rating. Tables and graphs were used to present and analyse data. The results reviewed shrinkage as a true challenge which undermines company performance and all efforts to boost performance.